Luteoloside Exerts Analgesic Effect in a Complete Freund’s Adjuvant-Induced Inflammatory Model via Inhibiting Interleukin-1β Expression and Macrophage/Microglia Activation - Shi, Chun-Yan; He, Xi-Biao; Zhao, Chao; Wang, Hui-Jing (Frontiers in Pharmacology, 2020)
Background: Flavonoid monomers are proved to have an anti-inflammatory effect and may also be promising for chronic pain treatment. In the present study, the analgesic effect and the relevant mechanisms of luteoloside, one of the flavonoid monomers, were investigated. Methods: The analgesic effect of luteoloside was first evaluated in complete Freud’s adjunct-induced inflammatory model by von Frey test and Hargreaves test in both male and female mice. The interleukin-1β levels in plantar tissue, serum, dorsal root ganglion, and the dorsal horn of the spinal cord were determined by enzyme-linked immunosorbent assay or immunofluorescence. The activation of macrophage/microglia was tested by Iba-1 staining. Results: Our data showed that luteoloside exhibited both acute and chronic analgesic phenotypes. Every single dose of luteoloside solution produced a transient analgesic effect, while a long-lasting analgesic effect with repeated administration. In combination with luteoloside, celecoxib achieved a similar analgesic effect with a lower dosage. Luteoloside inhibited interleukin-1β expression in plantar tissue, dorsal root ganglion, the dorsal horn of spinal cord and serum, after 14 days of continuous administration. Furthermore, our results also showed that the activation of macrophage/microglia in dorsal root ganglions were significantly inhibited 2 hours after each single dose in daily luteoloside administration and recovered to a higher level 6 hours later. These findings might be involved in the mechanisms of the acute analgesic effect of luteoloside. Conclusion: Luteoloside presents an analgesic effect via anti-inflammatory and other mechanisms such as inhibiting the activation of macrophage/microglia.